Atividade antimicrobiana de myrcia guianensis (myrtaceae) e de seus fungos endofíticos - Banhos, Elissando Fonseca dos (2011)
Beneficial interactions between plants and microorganisms have been investigated under different ecological, physiological, biochemical and genetic factors. However, the systematic exploration of biomolecules with the potential to result in biotech products from this interaction is still relatively scarce. This study aimed to evaluate the antimicrobial activity of secondary metabolites which make up the essential oil and extracts of Myrcia guianensis leafs, as well as to verify the antimicrobial activity of the secondary metabolites produced by their fungal endophytes. The plant tissues were collected in Santarém, Pará. The leaves of M. guianensis were used to obtain ethanolic, methanolic, hexane and ethyl acetate extracts, as well as the essential oil, apart from endophytic fungi, isolated from root, stem and leaf of this plant. The antimicrobial activity tests were performed using pathogenic strains of Pseudomonas aureuginosa, Staphylococcus aureus, Enterococcus faecalis, Bacillus cereus, Candida albicans and Penicilliun avelani. The isolated endophytic fungi were separated into groups considering its macro and micro-morphological features. Is was obtained 156 isolates distributed into 14 groups. The characteristics revealed the presence of genres such as Pestalotiopsis, Phomopsis, Aspergillus, Xylaria, Penicillium, and Fusarium. None of the plant extracts or the essential oil showed antimicrobial activity against the pathogenic strains. Of the metabolic media obtained from 46 endophytic fungi, three showed positive results against S. aureus, three had activity against E. faecalis, one showed activity against C. albicans and two showed inhibitory activity against the fungus P. avelani. The results of the antimicrobial activity of the metabolic media allowed to select the strain MgRe2 2.3 B for the subsequent steps, since the metabolic broth of this strain presented inhibition halo of 12.5 mm against S. aureus, 15.0 mm against E. faecalis and 43.3 mm against P. avelani. The extracts AEI1 and AE1 obtained from MgRe2 2.3 B showed the most promising results and were fractionated to initiate the identification of the bioactive molecule. The fractions were tested again, and the best results were observed within the fractions 1 and 2. The HPLC analysis showed that the substance 2 of the fraction 1 and the substance 3 of fraction 2 are the same substance. In tests to determine the MID, both fraction 1 and fraction 2 have showed inhibitory effect against S. aureus to the dose of 0,25 mg/mL. These fractions also showed inhibitory effect against P. avelani until the dose of 0,125 mg/mL. Against E. faecalis, fraction 1 showed an inhibitory effect until the dose of 0,50 mg/mL, while the fraction 2 showed until the dose of 1,0 mg/mL. For MBD or fungicide, both fractions 1 and 2 did not demonstrate bactericidal capacity against E. faecalis. Howrever, these fractions demonstrated bactericidal activity against S. aureus until a dose of 0,50 mg/mL. In the tests using P. avelani, the fractions showed fungicidal action only when both were at a dose of 1,0 mg/mL. The results show the potential of biotechnology endophytic fungi isolated from the plant species investigated.